Analisis Implementasi E-Bugdeting dengan Menggunakan Model CIPP pada Pemerintah Provinsi DKI Jakarta - Rama Andika Thio Rahman (Jurnal Sistem Informasi, 2018)
This study aimed to analyse the effectiveness of e-Budgeting implementation in the Provincial Government of DKI Jakarta by using CIPP (Context, Input, Process, and Product) model from Stufflebeam (2003). The type of this research was a qualitative research using case-study approach. The data were collected using interviews and documentation studies. The results of this study revealed that the implementation of e-Budgeting in DKI Jakarta Provincial Government was feasible to proceed as it was proven to be effective when viewed from the four components of CIPP Model that is context which focuses on the success of achieving the initial goal of budget transparency and accountability. Furthermore, in terms of inputs, the use of facilities, infrastructure and human resources was adequate. Viewed from the process, e-Budgeting simplified and minimized errors in the process of preparing the work plan and budget (RKA). From the output (Product), it improved the quality of regional budget (APBD) in terms of conformity with the Regional Medium-Term Development Plan (RPJMD) document and the control management of budget that plays an active role.